Enantioselective in vitro metabolism and in vitro-in vivo correlation of the herbicide ethofumesate in a human model - Perovani, Icaro Salgado; Carrão, Daniel Blascke; de Albuquerque, Nayara Cristina Perez; de Oliveira, Anderson Rodrigo Moraes [UNESP] (Elsevier, 2020)
Ethofumesate (ETO) is a chiral herbicide that is marketed as a racemic mixture in the European Union and the United States. The growing consumption of pesticides in the world, along with their presence in water and food, has increased human exposure to these chemicals. Another issue concerning these compounds is that each enantiomer of a chiral pesticide may interact with biomolecules differently. For this reason, this study aimed to investigate the in vitro metabolism of ethofumesate (the racemic mixture as well as the isolated enantiomers) by human liver microsomes (HLM) and to explore the in vitro-in vivo correlation. Before the kinetics was determined, the method was fully validated by evaluating its selectivity, linearity, precision, accuracy, carryover, and stability. All the evaluated parameters agreed with the European Medicines Agency guideline. The enzyme kinetic parameters and the in vitro-in vivo correlation demonstrated that there was no enantioselective difference for the metabolism and bioavailable fraction of each enantiomer. The enzyme kinetics was biphasic; the KM1 values were 15, 5.8, and 5.6 for rac-ETO, (+)-ETO, and (–)-ETO, respectively. The total in vitro intrinsic clearance was 0.10 mg mL min−1 mg−1 for rac-ETO and its enantiomers. The enantiomer (–)-ETO was only metabolized by CYP2C19, while (+)-ETO was metabolized by both CYP2C19 and CYP3A4. CYP2C19 polymorphism and/or inhibition may represent a risk for humans exposed to this pesticide.
Keywords: enantioselective in vitro metabolism; ethofumesate; GC-MS; Herbicide; human liver microsomes; in vitro-in vivo correlation